Peningkatan Keaktifan Mahasiswa melalui Penerapan Model Pembelajaran Berbasis Proyek - Rosmeli Rosmeli; Erfit Erfit; Fathiyah Fathiyah (Ekonomis: Journal of Economics and Business, 2023)
Regional Economics is a course that focuses on the spatial or spatial aspects of economic activity. In the initial process of teaching and learning in this course, the lecture system was used more, but after the middle examination, the lectures continued with theory and practice in calculating regional economic analysis tools. The project-based learning method is a good method to be used as a learning model that actively involves students. This study used an experimental research method with the research object being regional economics students in class R004, Faculty of Economics and Business, Jambi University. From the results of learning innovation activities in the Regional Economics, it is known that of the six indicators used there has been an increase in student participation in the learning process. Before the Pjbl the average of the six indicators was 48.96% and the average after the Pjbl was 83.11%